Stromal Myofibroblasts Accompany Modifications in the Epithelial Phenotype of Tongue Dysplastic and Malignant Lesions - Vered, Marilena (Springer Netherlands, 2009)
Stromal myofibroblasts (SMF) associated with various types of carcinomas are believed to emerge under the influence of the tumor cells. Recent studies have shown that SMF may originate from fibroblasts within the tumor stroma or even from carcinoma cells by the process of epithelial-mesenchymal transition. The aim of this study was to investigate the concomitant expression of epithelial membrane antigen and α-smooth muscle actin in cells at the tumor-connective tissue interface in human tongue carcinoma, as a possible reflection of epithelial-mesenchymal transition. Given its key role in this process, expression of transforming growth factor-β in the malignant cells was assessed as well. Immunostaining with α-smooth muscle actin was performed on cases of hyperplasia (n = 16), mild dysplasia (n = 12), moderate-to-severe dysplasia (n = 11) and carcinoma (n = 22). Transforming growth factor-β assessment and double immunostaining with epithelial membrane antigen and α-smooth muscle actin were performed only in cases of carcinoma. SMF were significantly associated with carcinomas, while their number in pre-malignant lesions (hyperplasia and dysplasia) was significantly lower (P < 0.001). Although SMF were found in all carcinomas, they were heterogeneous in their frequency and patterns of distribution. In addition, 95% of the carcinomas expressed transforming growth factor-β and 41% exhibited cells positive for both epithelial membrane antigen and α-smooth muscle actin. SMF were almost exclusively associated with established carcinomas and not with pre-malignant lesions. Cells that co-expressed epithelial membrane antigen and α-smooth muscle actin can be a manifestation of epithelial-mesenchymal transition and, as such, may serve as a source for SMF in these tumors. These findings appear to be linked to the frequent expression of transforming growth factor-β by the malignant cells.